Osteochondral lesions of the talus: diagnostic and therapeutic approaches in orthopedics - Pinheiro, Guilherme Lessa; Pereira, Alan Oliveira; Lima, Rosana Sampaio; da Fonseca, Rodrigo Jorge de Souza (Journal of the Foot & Ankle, 2025)
Objective: Evaluate the diagnostic and therapeutic approaches currently employed in the management of osteochondral lesions of the talus, with an emphasis on technological advances and regenerative therapies. Methods: This review was conducted based on the PRISMA guidelines and included 16 studies published between 2010 and 2024, selected from the PubMed, Scopus, Web of Science, and Embase databases. Results: Advanced imaging techniques, such as magnetic resonance imaging with T2 mapping and three dimensional computed tomography, are fundamental for early diagnosis and surgical planning. Conservative approaches, such as immobilization and physiotherapy rehabilitation, have demonstrated efficacy in providing symptomatic relief for minor lesions; however, they present limitations in tissue regeneration and the long-term maintenance of joint function. Conventional surgical procedures, including microfractures and subchondral perforation, were associated with initial functional improvements but with a risk of progressive degeneration of the reparative fibrocartilage. Regenerative therapies, such as autologous and allogeneic osteochondral transplantation, as well as the use of mesenchymal stem cells and bioactive scaffolds, have shown potential in restoring hyaline cartilage and preserving the joint, particularly in complex and refractory lesions. Despite technological and therapeutic advances, challenges persist, including the standardization of protocols, high costs, and limited accessibility to emerging therapies. Additionally, a meta-analysis was not possible to perform due to the heterogeneity of the included studies, which encompassed both randomized clinical trials and observational studies. Conclusion: Integrated and individualized therapeutic strategies are crucial for optimizing clinical outcomes, preserving joint functionality, and enhancing the quality of life for patients with osteochondral lesions of the talus. Level of evidence I; Systematic Review.